The Role of Traditional Laws and Taboos in Wildlife Conservation in the Oban Hill Sector of Cross River National Park (CRNP), Nigeria (2012)
Efforts to integrate rural people into biodiversity conservation through community-based conservation programs is an old tradition. These efforts were largely based on economic incentives, with little or no attention given to the role of culture and traditions in building support for conservation. Although these strategies are useful in promoting conservation and local empowerment, they are still fragile. Scholars suggest that incorporation of traditional values which reflect locally important cultural practices of the people into the management of conservation areas in Africa will help in their successful conservation. There is a strong need to assess cultural practices; traditional laws and taboos of the people in protected areas, and how they have assisted conservation in the past. To understand how such practices could be strengthened and incorporated into natural resources management and conservation strategies, there is a need to have a general overview of existing practices. The study analyzes the ways in which cultural practices and value systems of the people of Oban Sector of Cross River National Park Nigeria, have aided conservation in the past and how such practices can be encouraged, strengthened and replicated for sustainable natural resources management in the study area and possibly proposed for adoption elsewhere. Ten cultural institutions and seven laws and taboos which regulate the use of resources were recorded in the area. These laws and taboos were respected by all indigenes. Eleven animal species were found to be forbidden by the people. Some of the tabooed animals were for spiritual reasons while some were for medicinal purposes. Every community had sacred forests, called Mgbe forest (Eten Mgbe) The social organizations in the area ensured that these taboos are obeyed. Presence of other tribes, new religions/westernization, use of modern hunting equipments and poverty pose a threat to the effectiveness of these taboos as a conservation tool. Adaptation of some aspects of these taboos may be valuable for wildlife conservation, particularly in protected areas